Peroxin MoPex22 Regulates the Import of Peroxisomal Matrix Proteins and Appressorium-Mediated Plant Infection in Magnaporthe oryzae - Rangrang Chen; Kailun Lu; Lina Yang; Jihong Jiang; Lianwei Li (Journal of Fungi, 2024)
Magnaporthe oryzae, the pathogen responsible for rice blast disease, utilizes specialized infection structures known as appressoria to breach the leaf cuticle and establish intracellular, infectious hyphae. Our study demonstrates that the peroxin MoPex22 is crucial for appressorium function, specifically for the development of primary penetration hyphae. The ∆Mopex22 mutant exhibited slow growth, reduced aerial hyphae, and almost complete loss of virulence. Specifically, despite the mutant’s capability to form appressoria, it showed abnormalities during appressorium development, including reduced turgor, increased permeability of the appressorium wall, failure to form septin rings, and significantly decreased ability to penetrate host cells. Additionally, there was a delay in the degradation of lipid droplets during conidial germination and appressorium development. Consistent with these findings, the ΔMopex22 mutant showed an inefficient utilization of long-chain fatty acids and defects in cell wall integrity. Moreover, our findings indicate that MoPex22 acts as an anchor for MoPex4, facilitating the localization of MoPex4 to peroxisomes. Together with MoPex4, it affects the function of MoPex5, thus regulating the import of peroxisomal matrix proteins. Overall, these results highlight the essential role of MoPex22 in regulating the transport of peroxisomal matrix proteins, which affect fatty acid metabolism, glycerol accumulation, cell wall integrity, growth, appressorium development, and the pathogenicity of M. oryzae. This study provides valuable insights into the significance of peroxin functions in fungal biology and appressorium-mediated plant infection.